Speaking to Inspire: A Rhetorical Analysis of Jim Kwik’s Inspirational Speech - Gawi, Abdul; Waluyo, Untung; Fitriana, Eka; Soepriyanti, Henny (Program Studi Pendidikan Bahasa Inggris, 2025)
This research explores the rhetorical strategies employed by Jim Kwik, a motivational speaker and memory coach, focusing on his YouTube and podcast content. Grounded in classical and digital rhetoric theories, this study investigates how Kwik constructs digital ethos, pathos, and logos through verbal performance, sound cues, and narrative techniques. The article integrates Cicero's classical oratory principles, Aristotle's persuasive appeals, and Eyman's digital rhetoric framework to analyze Kwik's communication methods. Using a qualitative narrative approach and thematic analysis, five podcast episodes from